Hubungan Pola Makan dengan Kejadian Penyakit Hipertensi pada Lansia di Desa Manisrejo Kecamatan Taman Kota Madiun - Eny Pemilu Kusparlina (FORUM ILMIAH KESEHATAN, 2021)
Hypertension is a non-communicable disease, but hypertension is suffered by many people, the incidence of hypertension in the elderly becomes the highest. Asia has a record of 38.4 million hypertensive sufferers in 2000 and is predicted to be 67.4 million by 2025, while in Indonesia it reaches 17-21% of the population and most are undetectable. The purpose of this study was to determine the relationship between eating patterns and the incidence of hypertension in the elderly at Manisrejo Village, Taman, Madiun City. This was an cross-sectional study design. The sample of this study amounted to 60 elderly. This research instrument used questionnaires and measurement of hypertension using a spigmomanometer and stethoscope blood pressure measuring instrument. The analytical method used is Person Chisquare. The results of this study are p = Value of P = 0,000